Design of Home Automation System using Dual-Tone Multi-Frequency Technique - Chaudhary, Chandan; Kshetri, Alisha; Shrestha, Sujay Lal; Chapagain, Kamal (Himalayan Journal of Applied Science and Engineering, 2021)
With the growth of modern wireless technology and the advancement in the field of automation, a cost-effective home automation system to operate remotely located electrical appliances has been designed. The several technologies to design an automation system are identified and studied in the literature. Dual-tone multi-frequency (DTMF) technology has been identified to develop an automation system that can depict the picture of automation. The technology is identified to help elderly or physically challenged individuals to control the home appliances remotely. Thus, the DTMF automation technology has been implemented in a system. The study also focuses on saving energy by remotely switching the appliances on the state or off state as required. Android-based applications (Apps) has been implemented for simplicity. The app provides a convenient way to switch the appliances and lights on and off as required. This data from the app is further decoded and stored in the flip-flop and is used to trigger the relay through relay drivers. Based on the signal or the touch tones, the appliances are controlled. The system thus designed provides a wide range of coverage as it can be controlled remotely from any corner of the world with the availability of a GSM network.